Productivity and Efficiency Performance of the Malaysian Life Insurance Industry - Shazali, Abu Mansor; Alias, Radam (UKM, 2000)
This study attempts to measure the productivity of the life insurance industry by employing the non-parametric Malmquist Index approach. The finding shows that despite the productivity growth in the insurance industry, it is relatively low compared to the real economic growth experienced by Malaysia. Like the manufacturing sector, the future growth of this industry would depend on its ability to compete efficiently. Being able to provide service ill all efficient way would be an important source of comparative advantage under the era of globalization The results also suggest that both technical efficiency and technical progress contribute to the overall productivity growth of the industry.